IMPLEMENTASI PEMANTAUAN SUHU, KELEMBABAN DAN KADAR GAS AMONIA BERBASIS ANDROID PADA PETERNAKAN KAMBING SAPERA MITRA AGRO ABADI FARM - Mara, Muhlasah Novitasari (Jurnal Borneo Saintek, 2022)
The partner of this program is a dairy goat breeder Mitra Agro Abadi Farm which is located in Barukan Village, Semarang Regency. The fundamental problem of dairy goat farmers in Barukan Village is related to continuous real time monitoring of temperature, humidity and ammonia gas levels in goat cages. Breeders still use the manual method by estimating changes in temperature and humidity and changes in ammonia gas making the goat cage susceptible to disease in goats so that it affects the production of goat milk produced. Therefore, the PKM team offers a solution to create a system that can monitor temperature, humidity and ammonia gas levels in an Android-based goat pen that can be monitored via the farmer's cellphone, then the monitoring data is sent via the internet and then provides notifications to farmers remotely in real time. via mobile phones so that farmers can provide immediate handling or action if the cage conditions are not in accordance with ideal conditions. The goal to be achieved from this activity is that the Barukan Village goat breeders are IT literate and it is easier to control the condition of the goat cages in a measurable manner. Thus, the quality of goat's milk production also increases